Using of CALL Method in Writing - Emeliya Sukma Dara Damanik (Loquen, 2018)
This paper shares about using of CALL method in increasing English Writing Skill. The implementation of CALL method brings the new atmospheres in classroom and offers benefit to the increasing of four English skills. CALL method is an alternative tool to assist teacher or lecturer and student language learning. In spite of the benefits, the implementation of CALL method also has limitation. Therefore, teacher or lecturer should remind that CALL method can be applied depends on the situation suitable for the learners and their need